Diagnostic Accuracy of Ultrasound in Palpable Breast Lesions - Pathak, Manish Raj; Gautam, Mahesh; Bhandari, Rashmita (Birat Journal of Health Sciences, 2020)
Introduction: Breast carcinoma is the second leading cause of cancer related mortality in females around the world. Ultrasound plays a key role in differentiating cystic and solid lesions and is a convenient and non-invasive diagnostic tool to differentiate between benign and malignant lesions. Objectives: The aim of this study is to evaluate the diagnostic accuracy of ultrasound in palpable breast lesions. Methodology: A prospective cross-sectional study was carried out in patients with palpable breast lesions who presented in Department of radio diagnosis and imaging of Nobel Medical collegefor a period of one-year from February 2019- January 2020 using ultrasound. A total of 60 patientswereevaluated in the study. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated. Results: Out of 60 patients evaluated, ultrasound showed 46 (76.7%) cases to be benign and 14 (23.3%) cases to be malignant. FNAC revealed benign disease in 47 (78.3%) patients and malignant disease in 13 (21.7%) patients. The most common benign lesion was fibroadenoma. We found nearly 91.7% of the malignant lesions had spiculated margins and microcalcification. The sensitivity of ultrasound was 95.74% and specificity 92.3% with diagnostic accuracy 95%. Conclusion: Ultrasound is a convenient and non-invasive diagnostic tool with good sensitivity, specificity, positive predictive value, negative predictive value and accuracy in palpable breast lesions.